Challenges of sharing individual participant data for secondary research on neglected tropical diseases: the experience of Drugs for Neglected Diseases initiative and a call for action - Anastassia Negrouk; Thaddaeus Egondi; Craig Tipple; Justyna Tarwid; Michelle Childs; Dominique Junod-Moser (BMJ Open)
Introduction The Drugs for Neglected Diseases initiative (DNDi) is committed to maximising the scientific value of the individual participant data (IPD) it has collected during its 20 years of activity and the IPD it will collect in the future, while safeguarding research participants’ privacy and their right to know how their data will be processed.Objective The objective of this article is to share what DNDi has learnt while working on its commitment to data sharing. It also aims to advance the debate about best practice in the research community to avoid ‘IPD sharing paralysis’, with a focus on multistakeholder projects involving patients and researchers based in countries with various levels of data privacy regulations and measures.Results The article describes a practical case study outlining the ethical, legal and technical challenges encountered by DNDi in the context of IPD data sharing. The case study demonstrates that each individual research project presents new challenges, which frequently require external support, delaying the process of data sharing and increasing the overall cost.Conclusion These challenges mean that a case-by-case approach is required for each IPD project to ensure an appropriate balance between the rights of the individual, the integrity of the research and the maximum use of IPD for scientific progress. A collective and inclusive approach is needed to streamline the process of IPD sharing and accelerate research into pressing unmet medical needs.